Analysis of the Relation between Macroprudential and Microprudential Policy - Naďa Blahová (European Financial and Accounting Journal, 2015)
The article deals with the analysis of a relationship between macroprudential and microprudential policy on a general level and on an example of regulatorily required structure and volume of bank capital. Regulatory requirements and supervisory methods are described in connection with the institutional structure of regulation and supervision within the European economic area. An attention is paid to the development of supervision on an individual basis through consolidated supervision to supplementary supervision of financial conglomerates, which corresponds with the activity and structure of the financial sector, high rate of integration and transboundary action of financial groups headed by a bank. The European System of Financial Supervision and Single Supervisory Mechanism are presented. Development of the regulation of bank capital is analysed. The original microprudential approach is mentioned that involved macroeconomic impacts from its introduction. Based on the analysis of capital structure as conceived from Basel I to Basel III approaches of regulation to this important indicator are discussed. Instability sources and indicative instruments of macroprudential policy are analysed on an example of the excessive growth of credits and leverage as an instability source and countercyclical capital buffer, sectoral capital requirements and leverage ratio in the role of indicative instruments.
Keywords: G21; K23; 650; Bank; Capital; Macroprudential policy